Scalable slot-die coating of high performance perovskite solar cells. Issue 11 (14th August 2018) - Whitaker, James B.; Kim, Dong Hoe; Larson, Bryon W.; Zhang, Fei; Berry, Joseph J.; van Hest, Maikel F. A. M.; Zhu, Kai
Abstract : Perovskite based photovoltaic devices hold the promise to greatly reduce the cost of solar energy production; however, this potential depends greatly on the ability to deposit perovskite active layers using large scale deposition methods such as slot-die coating without sacrificing efficiency. Abstract : Perovskite based photovoltaic devices hold the promise to greatly reduce the cost of solar energy production; however, this potential depends greatly on the ability to deposit perovskite active layers using large scale deposition methods such as slot-die coating without sacrificing efficiency. Using a perovskite precursor ink with long wet-film processing window, we demonstrate efficient perovskite solar cells based on slot-die coated perovskite layer. We found almost no difference in the photophysical and structural details of perovskite films that were deposited by spin coating to films deposited by slot-die coating. We explored various slot-die coating parameters to determine their effect on the performance of the device metrics. In addition to slot-die coating, we demonstrate the versatility of this wide wet-film processing window by fabricating perovskite solar cells with active layers deposited by spin coating, blade coating, and spray coating that all exhibited similar performance.